OSCE : Status epilepticus - Kundan Mittal (Wolters Kluwer Medknow Publications, 2019)
Seizures are common cause of admission in PICU and also frequently seen after admission to PICU. Early identification and appropriate intervention are essential otherwise it mat lead to brain injury and multi-organ failure. It is also important to understand the pharmaco-kinetics and pharmaco-dynamics of antiepiletic drugs.